Determinants of sports injury in young female Swedish competitive figure skaters - Jederström, M.; Agnafors, S.; Ekegren, C.; Fagher, K.; Gauffin, H.; Korhonen, L.; Park, J.; Spreco, A.; Timpka, T. (British Journal of Sports Medicine, 2021)
Background Although figure skating attracts several hundred thousand participants worldwide, there is little knowledge about physical health and sports injuries among young skaters.